Explaining signals and systems with graphics and animations (I) - Chia, Marcus Jian Min (Nanyang Technological University, 2020)
This report focused on explaining Signals and Systems with Graphics and Animations for Electrical and Electronic Engineering students. The project showcased the implementation of MATLAB – App Designer in creating Graphical User Interfaces (GUI) for the users to understand the individual topics in Signals and Systems and Microsoft PowerPoint to develop step by step animated videos for students to learn the concepts better. With the help of MATLAB – App Designer software, it helped to consolidate all the GUI programs into one application for the students to use while learning. Moreover, students using the application will not only benefit them in understanding the concepts better, but it would be able to provide them with interactive functions for them to learn.